2019
DOI: 10.1111/ijmr.12202
|View full text |Cite
|
Sign up to set email alerts
|

Patent Litigation Strategy and Its Effects on the Firm

Abstract: Patent litigation has attracted scholarly attention to reconcile multiple views for new research. Accordingly, this paper addresses patent litigation strategy and its effect on the firm. Based on 106 papers and articles, six books, the author's logic and practice impressions, it first defines patent litigation strategy and differentiates similar concepts. Second, based on the process, the author fine‐tunes patent litigation strategy into three tactics: threat, filing and verdict. Then, she categorizes and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 102 publications
1
7
0
1
Order By: Relevance
“…They constantly track the changes in national public policies concerning animal welfare, public expectations, and the boundaries at what the courts can or will tolerate, then create the appropriate courtroom moments for new litigation strategies. In fact, we have observed comparable trends in the evolution of strategic litigation in other domains, such as intellectual property rights protection and environmental protection [63][64][65][66]. In this study, we notice and observe that a new litigation strategy themed in One Health is frequently used in civil lawsuit cases involving zoonotic diseases tactically.…”
Section: The Emerging Litigation Strategy Themed In One Health In Animal Health Lawsuitssupporting
confidence: 56%
“…They constantly track the changes in national public policies concerning animal welfare, public expectations, and the boundaries at what the courts can or will tolerate, then create the appropriate courtroom moments for new litigation strategies. In fact, we have observed comparable trends in the evolution of strategic litigation in other domains, such as intellectual property rights protection and environmental protection [63][64][65][66]. In this study, we notice and observe that a new litigation strategy themed in One Health is frequently used in civil lawsuit cases involving zoonotic diseases tactically.…”
Section: The Emerging Litigation Strategy Themed In One Health In Animal Health Lawsuitssupporting
confidence: 56%
“…The extant literature has shown that corporate lawsuits have a direct and significant impact on firms’ performances (Yang, 2019; Bagley, 2005), which makes us believe that to explore the antecedents of firms’ legal strategy. As the above analysis shows, executive legal expertise does matter in corporate legal strategy.…”
Section: Resultsmentioning
confidence: 99%
“…In the modern innovation economy, the competition for IP is becoming increasingly fierce, and the demand to understand its dynamics has grown significantly. Among other strategic elements, patent litigation is of great importance for firms due to its lengthy disputes, substantial costs, and enormous risks for both plaintiffs and defendants [6,7,8]. The network science approach to understanding inter-firm patent litigation relationships is of high significance.…”
Section: Introductionmentioning
confidence: 99%